Association between Legionella species and humic substances during early summer in the northern Baltic Sea - Eriksson, Karolina Ida Anna; Ahlinder, Jon; Ramasamy, Kesava Priyan; Andersson, Agneta; Sundell, David; Karlsson, Linda; Sjödin, Andreas; Thelaus, Johanna (Frontiers in Marine Science, 2023)
Climate change is projected to cause alterations in northern coastal systems, including humification and intensified nutrient loads, which can lead to ecosystem imbalances and establishment of new bacterial species. Several potential pathogens, such as different species of Legionella, hide in the environment between infections, some by living inside protozoan host cells. Knowledge about the occurrence of Legionella in natural waters is missing, which disable risk assessments of exposure. We performed a study of the species diversity of Legionella in the northern Baltic Sea (Gulf of Bothnia) during early summer to map their occurrence and to identify possible environmental drivers. We detected Legionella and potential protozoan hosts along gradients of the Gulf of Bothnia. We also for the first time present third generation full-length 16S rRNA amplicon sequencing (Nanopore) to resolve environmental species classification of Legionella, with a method suitable to study all bacteria. Our data show that full length 16S rRNA sequences is sufficient to resolve Legionella while the standard short Illumina sequences did not capture the entire diversity. For accurate species classification of Legionella, harmonization between the Nanopore classification methods is still needed and the bias toward the well-studied Legionella pneumophila need to be resolved. Different Legionella species occurred both in the Bothnian Sea and in the Bothnian Bay and their abundance were linked to humic substances and low salinity. The relative abundance of Legionella was higher in the humic-rich northern waters of the Bothnian Bay. The link between Legionella species and humic substances may be indirect via promotion of the heterotrophic microbial food web, allowing Legionella species and similar bacteria to establish. Humic substances are rich in iron, which has been shown crucial for growth of Legionella species and other pathogens. Considering climate change projections in this regional area, with increased humification and freshwater inflow, this bacterial niche containing potential pathogens might become more widespread in the future Baltic Sea. This study demonstrates the significance of DNA sequencing to monitor public health relevant bacteria like Legionella species in the environment. Including sequencing of bacteria and protozoa in the environmental monitoring programs could be used to identify ecosystem imbalances, which enable appropriate responses to emerging diseases.